Etyczne standardy relacji pomiędzy lekarzami a firmami farmaceutycznymi w Stanach Zjednoczonych - Makowska, Marta (Annales. Etyka w Życiu Gospodarczym, 2008)
This paper attempts an overview on the ethical issues of pharmaceutical industry gift-giving inthe United States of America. The article shows that law is not the only way in which the relationshipbetween physicians and pharmaceutical industry can be regulated.Most important professional associations of physicians, pharmacists, residents etc. considerindustry gifts as a conflict of interest. They created different ethical guidelines for this complicatedissue.The paper demonstrates various solutions of ethical matters in the relationship between physiciansand pharmaceutical industry by analyzing codes and guidelines of different associations. On the onehand it shows organizations which allow exchanging of gifts of no value. On the other hand it presentsassociations that forbid physicians accepting even a pen. The article also shows various attitudes ofthese associations to situations like inviting physicians to dinner, accepting drug samples, takingsubsidies from the company to defray the cost of the conference etc.The problem of those relations has been neglected for long time. From society’s point of view it isimportant for physicians to be informed about the rules and ways that pharmaceutical companies try toinfluence physicians’ prescription habits.